This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is a bit tricky question. But it can be solved. The question is :- n → ∞ lim n . sin ( 2 π 1 + n 2 ) Here comes the tricky part. We know that sin x = sin ( x − 2 n π ) . We are going to use this in the question. = n → ∞ lim n . sin ( 2 π 1 + n 2 − 2 n π ) = n → ∞ lim n . sin ( 2 π ( 1 + n 2 − n ) ) Rationalizing the part inside sin. = n → ∞ lim n . sin ( 2 π ( 1 + n 2 + n 1 ) ) = n → ∞ lim n . sin ( n 2 π n 2 1 + 1 + 1 1 ) Neglecting n 2 1 as it tends to 0. = n → ∞ lim n . s i n ( n π ) = π